2020
DOI: 10.2147/cia.s242113
|View full text |Cite
|
Sign up to set email alerts
|

<p>Spaced Retrieval and Episodic Memory Training in Alzheimer’s Disease</p>

Abstract: Introduction: This study replicated and extended the findings from the author's previous pilot study to further explore how a spaced retrieval (SR) memory training program might be effectively applied to help persons with Alzheimer's disease (AD) improve both short-and long-term recall of recent episodic events. Methods: A quasi-experimental within-subject group study was conducted with 15 participants with a diagnosis of AD. Results: Compared to a control condition, all participants were able to spontaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 91 publications
0
12
0
1
Order By: Relevance
“…Although our study was a quasiexperimental and controlled design with a reasonable number of subjects, it would be desirable to validate the system with patients suffering from certain types of neurodegenerative disease, such as Alzheimer's disease (AD). In our favor, recent studies have pointed out important improvements in the cognitive rehabilitation of this population, such as the study conducted by Small and Cochrane [63], where interventions with SR helped to maintain the functioning of recent episodic memory. The study by Hawley and Cherry [64] showed that the training with the SR technique had a positive influence in the recall of simple face-name associations.…”
Section: Discussionmentioning
confidence: 91%
“…Although our study was a quasiexperimental and controlled design with a reasonable number of subjects, it would be desirable to validate the system with patients suffering from certain types of neurodegenerative disease, such as Alzheimer's disease (AD). In our favor, recent studies have pointed out important improvements in the cognitive rehabilitation of this population, such as the study conducted by Small and Cochrane [63], where interventions with SR helped to maintain the functioning of recent episodic memory. The study by Hawley and Cherry [64] showed that the training with the SR technique had a positive influence in the recall of simple face-name associations.…”
Section: Discussionmentioning
confidence: 91%
“…The development of AID‐COMp was evidence‐based and employed a combination of methods. Aid‐COMp included: (1) learning how to use a memory book with the technique of spaced retrieval (Mahendra et al., 2011; Small , 2020); (2) improving lexical access using mixed semantic (Jelcic et al., 2012) and phonological (Neumann, 2018) therapy; (3) improving discourse expression and comprehension through the analysis of pictures and texts; and (4) the implementation of lexical access in PACE therapy (Coocks et al., 2013). AID‐COMp involved a total of 10 sessions delivered intensively, three times per week over 1 month.…”
Section: Aid‐comp Programme Overviewmentioning
confidence: 99%
“…For example, the spaced retrieval technique can improve episodic memory (Small and Coche, 2020). It involves recalling information at increasing time intervals to consolidate long‐term learning.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to controls, AD patients demonstrated better production of descriptions related to physical, social, and psychological self after autobiographical retrieval, suggesting the potential value to activate the sense of self in persons with AD. Additionally, spaced retrieval memory training studies have demonstrated the ability of AD patients to learn and recall new episodic information, which can improve short and long-term recall ( Small and Cochrane, 2020 ). Furthermore, there is evidence to support that certain aspects of selfhood, such as bodily awareness and social interaction (e.g., interpersonal self) remain preserved even in the final stages of the disease ( Lenzoni et al, 2020 ).…”
Section: Consciousness In Alzheimer’s Disease: Preserved Cognitions Emotions and Subjective Experiencementioning
confidence: 99%